2014
DOI: 10.1177/1362361314555146
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement with parents in 11-month-old siblings at high and low genetic risk for autism spectrum disorder

Abstract: Infant siblings of children with an autism spectrum disorder (ASD) are at heightened genetic risk to develop ASD. We observed high risk (HR, n =35) and low risk (LR, n =27) infants at 11 months during free play with a parent. Children were assessed for ASD in toddlerhood. HR infants with a later diagnosis (n = 10) were less socially engaged with their parents than were LR infants. Parent behavior during play did not vary by group. Within the HR group, ratings of social reciprocity at 11 months predicted Autism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 34 publications
(71 reference statements)
7
67
0
2
Order By: Relevance
“…In two prior reports from this study, with overlapping samples (Campbell et al 2015a, b), we found that HR infants with a diagnosis were less engaged with parents during free play at 11 months than either the LR or HR-noASD infants. At 22 months, they were also less likely to solicit their parents during an empathy probe when they were confronted with a “crying baby.” Thus, across three different types of laboratory situations and at two ages, HR siblings who received a diagnosis of ASD showed less interest in social interaction with their parents.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In two prior reports from this study, with overlapping samples (Campbell et al 2015a, b), we found that HR infants with a diagnosis were less engaged with parents during free play at 11 months than either the LR or HR-noASD infants. At 22 months, they were also less likely to solicit their parents during an empathy probe when they were confronted with a “crying baby.” Thus, across three different types of laboratory situations and at two ages, HR siblings who received a diagnosis of ASD showed less interest in social interaction with their parents.…”
Section: Discussionsupporting
confidence: 51%
“…Despite the group differences in children’s social interest and shared enjoyment with parents, the parents of the diagnosed children did not differ from the parents of LR children at either 11 (Campbell et al 2015a) or 22 months. At both ages, we rated parent behavior during a free play interaction using well-validated ratings of parent sensitivity and warmth as well as stimulation of cognitive development (NICHD ECCRN 1999).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Studying these infants allows for the prospective study of ASD. Previous research has found relatively comparable early language environments of infants with and without a family history of ASD [Campbell, Leezenbaum, Mahoney, Day, & Schmidt, ; Northrup & Iverson, ; Swanson et al, ; Talbott, Nelson, & Tager‐Flusberg, ], while some subtle differences in the timing and synchrony of parent–child interactions have been reported [Northrup & Iverson, ; Wan et al, ]. Studies of older children with ASD showed that responsive caregiver language was associated with better joint attention and language skills [Bottema‐Beutel, Yoder, Hochman, & Watson, ; McDuffie & Yoder, ; Siller & Sigman, , ].…”
Section: Introductionmentioning
confidence: 99%
“…high-risk siblings). High-risk siblings later diagnosed with ASD exhibit atypicalities in gaze-related behavior in the first year of life, including reduced frequency of eye contact (Bryson et al, 2007; Zwaigenbaum et al, 2005), joint attention (Ibañez et al, 2013), social engagement (Campbell et al, 2014), and attentiveness to a parent (Wan et al, 2013). A common scenario in research settings, in which conditions need to be standardized across participants, is to measure infant social-communication behavior with an unfamiliar examiner.…”
Section: Introductionmentioning
confidence: 99%